2020
DOI: 10.48550/arxiv.2007.04772
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of surface nanostructure and wettability on pool boiling: A molecular dynamics study

Abstract: We study the role of surface topology, surface chemistry, and wall superheat temperature on the onset of boiling, bubble nucleation and growth, and the possible formation of an insulating vapour film by means of large-scale MD simulations. In the numerical experiments, we control the system pressure by imposing a constant force on a moving piston. The simulations reveal that the presence of a nanostructure triggers the bubble formation, determines the nucleation site and facilitates the energy transfer from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Other studies on cavity effects have also been recently conducted, 33,34 stressing even further the importance of a surface post/defect in nucleate boiling. More specifically, Mukherjee et al 34 studied water bubble growth rate as a function of the notch geometry; the more recent work of Shahmardi et al 33 highlighted the importance of a surface defect (square cavities) in triggering the nanobubble nucleation, mainly focusing on the energy fields at constant cavity size. Further investigations have also been made by Zhou et al, 35 who conducted an interesting analysis on the non-trivial role played by the surface wettability in relation to different wall superheat values, in terms of nucleation time for flat surfaces.…”
Section: ■ Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Other studies on cavity effects have also been recently conducted, 33,34 stressing even further the importance of a surface post/defect in nucleate boiling. More specifically, Mukherjee et al 34 studied water bubble growth rate as a function of the notch geometry; the more recent work of Shahmardi et al 33 highlighted the importance of a surface defect (square cavities) in triggering the nanobubble nucleation, mainly focusing on the energy fields at constant cavity size. Further investigations have also been made by Zhou et al, 35 who conducted an interesting analysis on the non-trivial role played by the surface wettability in relation to different wall superheat values, in terms of nucleation time for flat surfaces.…”
Section: ■ Introductionmentioning
confidence: 97%
“…These investigations showed that the enhancement of thermal properties brought about by the surface roughness is also related to solid−liquid interactions. Other studies on cavity effects have also been recently conducted, 33,34 stressing even further the importance of a surface post/defect in nucleate boiling. More specifically, Mukherjee et al 34 studied water bubble growth rate as a function of the notch geometry; the more recent work of Shahmardi et al 33 highlighted the importance of a surface defect (square cavities) in triggering the nanobubble nucleation, mainly focusing on the energy fields at constant cavity size.…”
Section: ■ Introductionmentioning
confidence: 99%